Socialization and child rearing practices among Nigerian ethnic groups (2013)
Children are socialized into adult roles in society through the process of socialization particularly through the family which is the first contact point of any child into the open world of human relations. Socialization forms differ from one society to the other, in Nigeria there are three major ethnic groups in addition to about two hundred and forty seven minor ones, the pattern and forms of socialization among these ethnic nationalities differ. Ethnic identities and loyalty are built up in children in Nigeria based on these different cultural settings. Divergence in political and social relations including ethnic bigotry experience in the country in contemporary time has its root embedded in the differentiation existing in the nature and nurture of children at the formative stage of their lives. This paper examines the patterns of socialization and child rearing found among the various ethnic groups in Nigeria with a view to identifying lines of symmetry for the promotion of unity and oneness that will engender rapid and sustainable development in the country.